Economic Factors and Settings for Market Transformation in Asia - I. Espolov, Tlektes; T. Espolov, Aidos; S. Ospanov, Berick; G. Raiymbekov, Sailaukhan; K. Aituganov, Kairat; Zh. Suleimenov, Zhenisbek (International Journal of Supply Chain Management, 2019)
The Asian region as an economic powerhouse gains more importance every year: the population is becoming more affluent and the role of its markets is increasing on a global scale. This article analyzes the level of economic development of Asian countries. To determine the said level, the corresponding indicators were used, among them, GDP and GDP per capita, exports and imports, key partners in trade relations, the Economic Complexity Index, and the Logistics Performance Index. To order countries by the Economic Complexity Index and the International Logistics Performance Index, quadrants are constructed. The results indicate that Japan, Singapore and South Korea are countries with high scores for both indexes. Countries interested in importing goods but not holding strong positions in the Economic Complexity Index are India and Thailand. The main factors influencing the Asian market development are people’s diligence, international trade and investment. Along with investments, global production networks and supply chain management are crucial for the Asian market.